ANALISIS TINGKAT PENGETAHUAN PADA SOAL UAS PRODUKTIF OTOMOTIF SEMESTER GENAP 2024/2025 KELAS XII TKR SMK NEGERI TEKNOLOGI DI KOTA PADANG - Muhammad Al Adaby; Toto Sugiarto; Ahmad Arif; Muslim Muslim (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to analyze the distribution of factual, conceptual, procedural, and metacognitive knowledge levels in Final Semester Examination (UAS) questions for automotive productive subjects created by teachers at State Vocational High Schools (SMK) in Padang City. This research employs a quantitative descriptive design with a single variable of knowledge level based on Anderson's taxonomy. The research objects include 160 multiple-choice questions from the even semester UAS 2024/2025 from four State Vocational High Schools in Padang (SMKN 1 West Sumatra, SMKN 1 Padang, SMKN 5 Padang, and SMKN 8 Padang). The research instrument uses knowledge level analysis sheets based on operational verbs and question contexts. Data analysis techniques employ quantitative descriptive analysis by calculating the percentage of each knowledge level. The results show the overall distribution of knowledge levels: conceptual 49.375% (79 questions), procedural 18.75% (30 questions), factual 16.25% (26 questions), and metacognitive 15.625% (25 questions). There are significant variations among schools, particularly at SMKN 1 Padang with 70% conceptual dominance and SMKN 5 Padang with 30% metacognitive. Compared to BSNP (2018) recommendations, significant deviations occur where conceptual far exceeds standards (49.375% vs 10-20%) and procedural is below standards (18.75% vs 50-60%). However, these differences can be explained by the characteristics of vocational education that integrates written and practical assessments. This study recommends the need for teacher training in developing Bloom taxonomy-based questions, developing standardized question banks, and adjusting knowledge level distribution standards specific to vocational education.Keywords: knowledge levels, Anderson's taxonomy, final examination questions, automotive vocational education, HOTS